Tren Penelitian Industry 4.0 di Sektor Manufaktur: Analisis Bibliometrik - Fadlan, Ananda; Ramadhan, M Dhiky; Syauqi, Mhd Dzaki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze research trends and developments related to Industry 4.0 in the manufacturing sector using a bibliometric approach. Data were collected from the Scopus database covering the last five years (2022–2026), resulting in 1,660 articles for analysis. The analysis was conducted through descriptive analysis and bibliometric mapping using VOSviewer to identify keyword relationships, research clusters, and thematic trends. The results indicate that Industry 4.0 is the central theme, strongly connected with internet of things, decision making, and production process. Furthermore, emerging topics such as digital technologies, sustainability, and supply chains represent recent research focuses. These findings demonstrate that Industry 4.0 research in manufacturing is multidisciplinary and increasingly oriented toward sustainability and integrated industrial systems.